2009
DOI: 10.2308/jmar.2009.21.1.179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Existence and Identity of Major Customers on Supplier Profitability: Is Wal-Mart Different?

Abstract: We investigate how buyer power in the retail market affects suppliers' profitability. Buyer power exists when suppliers depend on a concentrated set of retailers. Further, Wal-Mart, the world's largest retailer, possesses additional buyer power because it has a dominant position in many product supply chains, advanced inventory management practices, and cutting edge technology. We form a sample of firms that supply retailers and utilize the major customer disclosure (SFAS No. 131) to proxy for dependence on ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 0 publications
2
53
1
Order By: Relevance
“…It is well known that the bargaining power of buyers arises when there are few large buyers and many small sellers, when the buyers of a company are large customers (i.e., they purchase large quantities), and when buyers can easily switch suppliers at low cost. These findings are similar to those of Gosman and Kohlbeck (2009), who found that, as sales to major customers increase, supplier gross margins and return on assets decrease. Moreover, as stated by Maloni and Benton (2000), exploitation of the supply chain by the powerful partner may lead to dissension and underperformance.…”
Section: Discussion Of Resultssupporting
confidence: 79%
“…It is well known that the bargaining power of buyers arises when there are few large buyers and many small sellers, when the buyers of a company are large customers (i.e., they purchase large quantities), and when buyers can easily switch suppliers at low cost. These findings are similar to those of Gosman and Kohlbeck (2009), who found that, as sales to major customers increase, supplier gross margins and return on assets decrease. Moreover, as stated by Maloni and Benton (2000), exploitation of the supply chain by the powerful partner may lead to dissension and underperformance.…”
Section: Discussion Of Resultssupporting
confidence: 79%
“…Major customers with strong bargaining power can also extract significant price concessions, which can significantly diminish gross margins for suppliers (Schumacher ; Snyder ). Their strong bargaining position can also result in major customers securing extended payment periods and larger trade credit, which can further heighten cash flow risks for the supplier firm (Gosman and Kohlbeck ; Kim and Henderson ). Consistent with this line of reasoning, Kim () and Gosman and Kohlbeck () report that sales to major customers are associated with lower supplier gross margins and profitability.…”
Section: Background and Literaturementioning
confidence: 99%
“…Prior studies of information externalities focusing on customers and suppliers include Olsen and Dietrich 1985, examining the impact of the monthly sales announcements of four large retailers on their suppliers’ returns; Raman and Shahrur 2008, studying the determinants and consequences of earnings management by firms in the context of customers and suppliers; Gosman and Kohlbeck 2009, examining how buyer power in the retail market affects suppliers’ profitability; Patatoukas 2010, exploring how customer‐based concentration affects suppliers’ stock market valuation; Hertzel, Li, Officer, and Rodgers 2008, investigating the response of customers and suppliers of firms that declare bankruptcy; and Cohen and Frazzini 2008, exploring a trading strategy based on customers’ news events. We add to this literature by developing hypotheses and providing evidence on how the information externality suppliers experience at the time of their customers’ earnings announcements varies as a function of: (1) the magnitude of the information disclosed by customers; (2) the strength of the economic bond between customers and suppliers; (3) the components of customers’ earnings; (4) the level of macroeconomic uncertainty; and (5) the earnings persistence of suppliers and customers.…”
Section: Prior Research and Hypothesis Developmentmentioning
confidence: 99%